Tingkat Kelulushidupan Karang Acropora jacqulineae pada Fragmentasi dan Transplantasi di Dalam dan Luar Air - Widiastuti, Widiastuti (Journal of Marine and Aquatic Sciences; Vol 5 No 2 (2019), 2019)
Coral transplantations are widely conducted at the coastal areas where corals are both fragmented and transplanted out of the water, exposed to open air and sunlight directly. However, the effectivity of these methods remain poorly understand due to different physiological type of corals. Coral Acropora jacqulineae is one of common transplanted coral for ornamental aquarium. The aim of this reseach was to examine the survival rates of fragmented and transplanted A. jacqulineae both in the water and out of the water. Each coral donor was fragmented with different initial sizes (3, 5 and 7 cm). All the fragments were cemented on the artificial substrate and arranged on the metal table which has been set on the sea floor at 15 m prior to the experiment. The survival rates were measured in every month for 9 months. The differences of the survival rates of fragmented and transplanted coral fragments both in the water and out of the water were analysed by using Fisher’s Exact test ( P = 0.05). According to Fisher’s Exact test that the survival rates of coral A. jacqulineae fragmented and transplanted both in the water and out of the water were no significantly different. It is suggested that this condition occured within 2 hours. Therefore, coral A. jacqulineae is one of the coral that can be used in transplantation activity where coral takes out of the water. Nevertheless, this activity has to be done within 2 hours, otherwise it may bring lethal effect to the coral`s metabolism due to stress.